Molecular testing for adolescent and young adult central nervous system tumors: A Canadian guideline - Lim-Fat, Mary Jane; Macdonald, Maria; Lapointe, Sarah; Climans, Seth Andrew; Cacciotti, Chantel; Chahal, Manik; Perreault, Sebastien; Tsang, Derek S.; Gao, Andrew; Yip, Stephen; Keith, Julia; Bennett, Julie; et al. (Frontiers in Oncology, 2022)
The 2021 World Health Organization (WHO) classification of CNS tumors incorporates molecular signatures with histology and has highlighted differences across pediatric vs adult-type CNS tumors. However, adolescent and young adults (AYA; aged 15–39), can suffer from tumors across this spectrum and is a recognized orphan population that requires multidisciplinary, specialized care, and often through a transition phase. To advocate for a uniform testing strategy in AYAs, pediatric and adult specialists from neuro-oncology, radiation oncology, neuropathology, and neurosurgery helped develop this review and testing framework through the Canadian AYA Neuro-Oncology Consortium. We propose a comprehensive approach to molecular testing in this unique population, based on the recent tumor classification and within the clinical framework of the provincial health care systems in Canada. Contributions to the field While there are guidelines for testing in adult and pediatric CNS tumor populations, there is no consensus testing for AYA patients whose care occur in both pediatric and adult hospitals. Our review of the literature and guideline adopts a resource-effective and clinically-oriented approach to improve diagnosis and prognostication of brain tumors in the AYA population, as part of a nation-wide initiative to improve care for AYA patients.